(untitled) (Research, Society and Development, 2024)
The Stromal Vascular Fraction (SVF) and nanofat are products of the extraction of regenerative cells from adipose tissue, mainly, or bone marrow. The biggest difference between them is whether or not enzymes are used to obtain these products. Therefore, the objective of this research is to discuss whether or not there is a difference between these techniques, enzymatic or mechanical, in the context of scarring and surgery. Methods: This article carried out under the systematic review model, using the electronic databases Pubmed, Scielo and Elsevier. Papers published from 2010 to 2014 in English or Portuguese were included. Results: FVE has a greater quantity of progenitor cells, being more effective, especially in the early stages of healing. Nanofat has the great advantage of, in addition to good amounts of growth factors and cytokines, lower legal implications. Conclusion: Therefore, there is apparent superiority of the enzymatic form over the mechanics, but more comparative studies are needed for this phenomenon to be confirmed, especially when taking into account that there are few studies that compare the two modalities.